HANIF DALAM KONSEP AL QURAN - Mubarak Bakri (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2019)
This article discusses the main problem that is how the nature of hanif in the view of the Koran, both in terms of forms of expression, types, and their influence in social life. The word hanif is usually interpreted as